ANALISIS PERSEPSI MAHASISWA TERHADAP PRAKTIKUM DI RUMAH SELAMA MASA PANDEMI COVID-19 PADA MATA KULIAH FISIOLOGI TUMBUHAN - Nur Muhajirah Yunus; Sukmawati syam (Universitas Cokroaminoto Palopo, 2021)
This study aims to determine student perceptions of practicum at home during the Covid-19 pandemic in the Plant Physiology Course. This type of research is descriptive qualitative research. The sample in this study were students of the 2018 Biology Education Study Program who programmed the Plant Physiology Course as many as 22 people. Samples were taken using simple random sampling technique. Data collection techniques were carried out by filling out questionnaires through Google Forms and interviews with several students to find out the obstacles in online practicum (at home). The results showed that students' perceptions of online practicum (at home) during the Covid-19 pandemic in the Plant Physiology Course overall obtained 63.10% results in the poor category. The main obstacles faced by students are the availability of tools and materials, the form of the lecturer's explanation regarding the practicum procedure is still not optimal, the instability of the internet network, limited quota, the influence of gadged quality, and students do not read the theory that is in line with the practicum material so they do not understand the purpose of the practicum.